Superconductivity in Layerd Cuprate - Abd Shukor, Roslan; Kek, C. A.; Yeoh, W. K. (Universiti Putra Malaysia Press, 2005)
A series of layered cuprate (Rut_xNb)Sr2GdCups (Ru1212) for 0 :5 x :5 1 has been synthesized by the solid state reaction method. Powder X-ray diffraction analysis indicates that oxygen flow is important in the formation of the Ru1212 phase and superconductivity in the system. Samples with nominal composition (Rul_ x b)Sr2GdCu20 S can be indexed as a tetragonal structure with space group P4/mmm. The undoped compound exhibits the highest superconducting transition with Tc onsel of 65 K and Tc zero of 55 K. Our results also show that doping with b decreases the normal state conductivity and suppresses superconductivity in the system.